Konsep Tawakal dalam Kitab Tanwirul Qulub: Analisis Isi dan Relevasinya bagi Kehidupan Modern - Muhamad Zidan Alida Putera; Anisa Rihadatul A’isy; Iffan Ahmad Gufron; Ade Fakih Kurniawan (Hikamia: Jurnal Pemikiran Tasawuf dan Peradaban Islam, 2026)
The concept of tawakal is one of the main teachings in Islamic spirituality that plays an important role in shaping inner peace and emotional balance. In modern life, which is characterized by psychological pressure, materialistic orientation, and spiritual crisis, tawakal has become a relevant religious value to be reexamined. This study aims to analyze the concept of tawakkul in the book Tanwirul Qulub by Shaykh Muhammad Amin Al-Kurdi and to explain its relevance to contemporary life. This research employs a qualitative method with a descriptive-analytical approach. Data were collected through library research, using Tanwirul Qulub as the primary source and various scholarly books and journals as secondary sources. Data analysis was conducted using content analysis to reveal the conceptual and practical meanings of tawakal. The results indicate that the value of tawakal helps individuals avoid materialistic lifestyles, reduce envy toward others, and better manage emotions such as disappointment, anxiety, and anger. The concept of tawakal in Tanwirul Qulub is not only relevant as a classical Sufi teaching but also serves as a practical guide for addressing psychological and spiritual problems in modern society.